Mechanism of electroacupuncture on rats with primary dysmenorrhea based on microRNA expression spectrum and PI3K/Akt/mTOR signaling pathway - Si-an PAN; Shao-hua WANG; Han-yu YUAN; Juan LI; Xiao XUE; Zeng-hui YUE; Yu LIU (World Journal of Acupuncture - Moxibustion)
Objective: To investigate the effect of electroacupuncture (EA) on microRNA (miRNA) expression spectrum and PI3K/Akt/mTOR signaling pathway in uterine tissue of rats with primary dysmenorrhea (PDM), and to explore the potential mechanism of EA in the treatment of PDM. Methods: Thirty female SD rats, weighted (200 ± 20) g were randomly divided into control group, model group and EA group, 10 rats in each group. By using subcutaneous injection of estradiol diphenhydrate combined with intraperitoneal injection of oxytocin, PDM models were established. Rats in the EA group received EA at “Sanyinjiao”(SP6) and “Guanyuan”(CV4) at dense waves and a frequency of 50 Hz, once a day, 20 min each time, for 10 consecutive days. After the 10-day intervention, samples were collected and transmission electron microscopy was used to observe the ultrastructural changes of the cells in uterine tissue in each group. With RNA-seq method, the changes of miRNA expression spectrum in rat uterine tissue were detected. Bioinformatics analysis such as GO functional annotation and KEGG pathway was performed according to differentially expressed miRNAs. Differentially expressed miRNAs were verified by qRT-PCR. Endometrial stromal cells were selected as the target cells and transfected; and they were divided into control group, NC mimics group, mimic miR-144–3p group, NC inhibitor group and inhibitor miR-144–3p group. The apoptosis was determined by using flow cytometrydetect apoptosis, the miRNA and protein expression of PI3K/Akt/mTOR signaling pathway were detected by qRT-PCR and Western blot in each group separately. Results: 1. Transmission electron microscope. (1) Control group: no obvious morphological changes in the uterine tissue. (2) Model group: fibroblasts in uterine tissue were irregular, the edema was presented in cellular cytoplasm, the nuclei were irregular and mitochondria swollen seriously; the rough endoplasmic reticulum was expanded moderately. (3) EA group: fibroblasts were spindle-shaped and pyknotic, the cytoplasm increased in electron density, the nuclei were slightly irregular and pyknotic, mitochondria were oval in shape, with little swelling and vacuolation; the rough endoplasmic reticulum was expanded slightly and retained, with a small amount of degranulation. 2. Compared with the control group, there were 26 differentially expressed miRNAs in the uterine tissue of rats with PDM. After EA intervention, the expression of miR-144–3p was significantly up-regulated. GO functional analysis of differentially expressed miRNAs in PDM rats after EA showed that the biological functions involved calcium transmembrane transporter activity, mitogen-activated protein kinase binding, epithelial cell migration, tissue migration, etc. 3. KEGG pathway analysis showed that PI3K/Akt signaling pathway, MAPK signaling pathway and calcium signaling pathway were enriched. Mimic miR-144-3p increased the apotosis of endometrial stromal cells, and decreased the mRNA and protein expression of PI3K,Akt, and mTOR (P < 0.01). Conclusion: EA can optimize the cell morphology in the uterine tissue of rats with PDM and affect the miRNA expression spectrum, which may be associated with the effect of EA for up-regulating miR-144–3p expression in endometrial stromal cells, suppressing PI3K/Akt/mTOR signaling pathway and causing apoptosis.